PRIMUL CURS ONLINE PENTRU BIBLIOTECARI – DREPTUL DE AUTOR PENTRU BIBLIOTECARI - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2020)
The article describes the event where the Romanian version of the “Copyright for Librarians: an online open curriculum in copyright law” curricula was launched. The curricula will be part of the Legal Framework for Libraries Course at the Bachelor Program and also within the Digital Libraries and Copyright Issues Course at Master Program. At the event, Certificates of appreciation were presented to students from the Department of Translation, Interpretation and Applied Linguistics at Moldova State University for translation. The certificates were co-signed by EIFL and Harvard’s Berkman Center for Internet and Society who developed the curriculum, and were presented by associate professor Nelly Turcan, vice-dean of the Faculty of Journalism and Science of Communication and Mariana Harjevschi, vice president of the Library Association from Moldova. The event took part at the School of Library and Information Assistance at Moldova State University and have been attended by members of the Electronic Resources for Moldova Consortia, as well as library students. The Romanian version of the course will be available under a Creative Commons license in MediaWiki, the online learning platform supported by EIFL.